Biomassa e nutrientes em um povoamento de Eucalyptus saligna Smith submetido ao primeiro desbaste - Beulch, Lien da Silveira (2013)
Eucalyptus is one of the most cultivated species in Brazil due to its fast increment and adaptation to the various types of soils and its characteristics related to the climate. In the county of Rio Grande do Sul (RS), the area of forestry planting has expanded taking over areas where previously were used for agriculture and cattle. Therefore it has been made necessary the development of researches that aim to fully establish the cultivation of Eucalyptus saligna in a sustainable way. The present study had the objective to quantify the biomass and the storage of nutrients of an area planted with Eucalyptus saligna which had its first thinning in São Francisco de Assis RS. The data was collected in a plot which is 4 years old, situated in an area which has low fertility soil, in the farm Estancia das Oliveiras, which belongs to the company Stora Enso. In total it was selected nine trees to sample. The destructive sampling consisted of the individualization of compartments of the biomass presented over the soil (leaves, twigs, bark and wood). The collection of samples aimed to determine the quantity of dried material in the different compartments of Eucalyptus saligna. The production of biomass in the clear- cutting was 88.81 Mg ha-1, showing the following percentage of distribution: 76.8% in the wood, 9.3% in the bark, 7.9% in the twigs and 6.0% in the leaves. The capacity of storage of elements by the biomass presented the following decreased order of accumulation of macronutrients Ca > K > N > Mg > P > S and Mn > Fe > B > Zn > Cu of micronutrients. In the occasion of the thinning of 40% of the plot, the production of biomass was 35.52 Mg ha-1. When it was solely done the collection of the commercial wood and bark (d≥ 8 cm), the biomass left in the field would contribute with 60.2% of the macronutrients and 59.9% of the micronutrients. Removing only the commercial wood, the percentage of nutrients left in the field raises to 80.5% of macronutrients and 88.4% of micronutrients. Independently on the chosen system, the most limiting nutrient for the next rotations would be Potassium. In ecological terms, the process that would least export nutrients from the system would be the one in which you would only collect the commercial wood, living the other components such as leaves, twigs and bark in the soil as a forestry waste.